Entrepreneurial Performance Model: A Business Perspective in the Digital Economy Era - Deri Firmansyah; Rahma Wahdiniwaty; Isniar Budiarti (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
The adequacy of digital literacy (DL) among entrepreneurs can trigger the birth of readiness and ability to carry out digital transformation (DT) in relevant business processes and models in the digital economy era to improve entrepreneurial performance with better competitiveness. Also the existence of an entrepreneurial commitment to market orientation (MO) will facilitate business success. This research identifies and explores entrepreneurial performance (EP) models in the digital economy era in terms of DT, DL and MO mediation. The path analysis model was used to test the combined interaction of DT and DL with EP, and the MO relationship that mediates all three. The findings, DT and DL had a significant positive effect on MO both individually and jointly. DT directly has a significant positive effect on EP, also DL directly has a significant positive effect on EP. Sobel test results, it is known that DT has an insignificant positive effect on EP through MO, while DL has a significant positive effect on EP through MO. MO has the mediating effect of DT and DL relationships in influencing EP, consequently MO has a positive impact on EP. This research offers a framework for the performance model of entrepreneurship in a business perspective in the era of the digital economy. The adoption and modification of marketing mix factors into new marketing mix models is necessary to support the implementation of strategies and practices. An exploration of the influence of innovative new marketing mix models on DT practices, DL readiness and MO clarity in the context of entrepreneurship, as well as their implications for business performance, can be considered as future research directions.